The Role of BPOM in The Circulation of Traditional Medicine in Surakarta - Ulung Ajubah Tri Atmojo; Marisa Kurnianingsih; H Hartanto (Universitas Muhammadiyah Surakarta, 2023)
The aim in question is what is the role of BPOM and what obstacles are faced in overcoming the circulation of traditional medicines. Many illegal traditional medicines are circulating, causing problems in Surakarta society. This research uses empirical juridical methods. This research produces what the main roles are in BPOM Surakarta and the community in educating about illegal traditional medicines that are widely circulating in the community and how to deal with this.